Sustained effects of a psychoeducational group intervention following bariatric surgery: follow-up of the randomized controlled BaSE study - Wild, Beate; Hünnemeyer, Katharina; Schellberg, Dieter; Müller, Beat P.; Herzog, Wolfgang (Surgery for obesity and related diseases, 2017)
Background Evidence regarding the efficacy of psychosocial interventions after bariatric surgery is rare and shows conflicting results. Objectives The Bariatric Surgery and Education (BaSE) study aimed to assess the efficacy of a psychoeducational group intervention in patients after bariatric surgery. Setting The BaSE study was a randomized, controlled, multicenter clinical trial involving 117 patients who underwent bariatric surgery. Patients received either conventional postsurgical visits or, in addition, a 1-year psychoeducational group program. The present study evaluated the sustained effects of the intervention program. Mean follow-up duration was 37.9 months (standard deviation [SD] 8.2 months) after surgery. Methods Outcome measures were as follows: body mass index (BMI), weight loss, self-efficacy, depression severity, and health-related quality of life (HRQOL). Groups were compared using an intention-to-treat approach with a mixed model for repeated measurements. Results A total of 74 patients (63.2%) completed the follow-up (T5) assessment. Mean weight loss for all patients was 43 kg (SD 15.5 kg) at T5 (mean BMI 35.1 kg/m2). Mean excess weight loss was 60.4%. The effects of the surgery during the first postsurgical year were reflected, on average, by both decreasing weight and psychosocial burden. At the T5 time point, patients had slowly started to regain weight and to deteriorate regarding psychosocial aspects. However, at T5, patients who had participated in the intervention program (n = 39) showed significantly lower depression severity scores (p = .03) and significantly higher self-efficacy (p = .03) compared to the control group (n = 35). The 2 groups did not differ regarding weight loss and quality of life. Conclusion Psychoeducational intervention shows sustained effects on both depression severity scores and self-efficacy.